Mixed Reality Game YU-GI-OH - Violla Gunova (Universitas Pendidikan Indonesia (UPI), 2022)
Mixed Reality is a technology that combines the real world with the virtual world. Merging these two worlds will form a new environment where each object from each world can interact with each other. This technology will offer a different user experience depending on how it is used, including digital games. This paper will discuss how to construct the card along with its mechanism of movement that used in YU-GI-OH game and its implementation on mixed reality technology using the HoloLens platform. The game be integrated to HoloLens until view stage.